O1-S10.02 HIV and bacterial STI testing among men who have sex with men in the USA. (10th July 2011) - Rosenberger, J G; Van Der Pol, B; Herbenick, D; Novak, D S; Reece, M; Fortenberry, J D
Abstract : Purpose: Growing literature has documented the extent to which bacterial sexually transmitted infections (STI) facilitate transmission/acquisition of HIV. Due to the disproportionate impact of HIV on men who have sex with men (MSM), public health messaging encourages routine STI and HIV screening among this population. This study sought to document testing behaviours among MSM in the US and understand factors associated with STI testing. Methods: Data were collected via an internet survey from 27 756 18–80 year old MSM members of an online sexual networking website. Measures included sociodemographics, STI/HIV testing behaviours, STI/HIV diagnoses, and lifetime sexual behaviour history. Results: Participants' mean age was 39.0 years, ethnicities included white (84.5%), Latino (6.4%), African American (3.5%), and most (79.9%) identified as homosexual. Over half (54.2%) indicated they were not in a romantic relationship, and nearly all (88.9%) had been sexually active with more than one partner in the past year. Testing rates (past year) were similar for both HIV(65.4%) and STI (60.8%), yet testing in the past 6 months differed with men reporting more frequent STI testing (63.8%) compared to HIV (46.5%); rates of infection in the previous 2 years included gonorrhoea (4.5%), Chlamydia (4.1%), and HIV (3.2%), with lifetime HIV infection rate being 12.5%. Among men living with HIV infection, rates of bacterial STI testing in the past year were higher (76.1%), with gonorrhoea and Chlamydia rates being 8.6% and 7.6% respectively. Both race and sexual orientation were predictive of bacterial STI testing in the past year, with non-white and bisexual men being less likely to have done so (p<0.01). Conclusions: These data provide a large scale assessment of HIV and STI testing among MSM in the US Findings from this study highlight gaps in screening between bacterial STI and HIV and suggest a need to promote services that offer HIV and STI testing simultaneously.